1985
DOI: 10.1116/1.573186
|View full text |Cite
|
Sign up to set email alerts
|

The effect of low temperature annealing on defects, impurities, and electrical properties of (Hg,Cd)Te

Abstract: Many methods for the preparation of (Hg,Cd)Te alloys rely on a low temperature processing step to convert the as-grown p-type material to n-type, or to otherwise adjust the concentration of native acceptors. During this anneal, tellurium precipitates in the material are annihilated by in-diffusing mercury, resulting in a substantial multiplication of dislocations. For substantially long anneals (>1 day at 270 °C) the depth of the p–n junction is found to vary as the square root of the anneal time and in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
33
0

Year Published

1987
1987
2010
2010

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 72 publications
(35 citation statements)
references
References 0 publications
2
33
0
Order By: Relevance
“…Consequently, taking into account the constant source of Cd at the surface, the Cd flux reaching the p-n junction diminishes. The stronger Cd i annihilation results in a progressive retardation of the p-n junction propagation contrary to the standard models of the p-to-n conversion, 15,16 which assume annihilation of Cd i only close to the p-n junction. An argument for the support of the presented view can be deduced from the undulation of the p-n junction contour (Fig.…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…Consequently, taking into account the constant source of Cd at the surface, the Cd flux reaching the p-n junction diminishes. The stronger Cd i annihilation results in a progressive retardation of the p-n junction propagation contrary to the standard models of the p-to-n conversion, 15,16 which assume annihilation of Cd i only close to the p-n junction. An argument for the support of the presented view can be deduced from the undulation of the p-n junction contour (Fig.…”
Section: Discussionmentioning
confidence: 81%
“…We expect that the purification occurs by gettering of fast diffusing elements (Na, Li, Cu, Ag) to the core, which was formerly observed in radiotracer diffusion experiments. 10,15 Residual donors from A-centers or group-VII donors in Te sublattice (Cl Te , Br Te , . .…”
Section: Discussionmentioning
confidence: 99%
“…16,17 A combination of all four mechanisms is likely with the sample history determining the dominant factor. Since no cap was grown on these samples, the cap/base interface can be ruled out as a contributor.…”
Section: Discussionmentioning
confidence: 98%
“…As the precipitate grows, it is observed that dislocation climb occurs as a result of the precipitation of the metal vacancies. 2 During the low-temperature anneal, the precipitation process rapidly comes to completion, and in the bulk of the material, the metal-vacancy concentration rapidly attains a value characteristic of the material under tellurium-saturated conditions at the low temperature. For example, if the anneal is performed at 270°C, the metal-vacancy concentration within the bulk of HgCdTe will reach a magnitude of ∼2 × 10 16 cm -3 .…”
Section: Methodsmentioning
confidence: 99%
“…A significant amount of work has been performed concerning the electrical properties of the materials following the anneal. [2][3][4][5][6][7] Most of these investigations were concentrated on long-wavelength infrared (LWIR) HgCdTe (x = 0.20-0.24), 2,3,5 though some investigations extended these to mid-wavelength infrared (MWIR) HgCdTe (x = 0.25-0.34). 4,6 Very few of these studies were extended to short-wavelength infrared (SWIR) HgCdTe (x > 0.34).…”
Section: Introductionmentioning
confidence: 99%